News media and the neoliberal privatization of education - Wubbena, Zane C.; Ford, Derek, 1985-; Porfilio, Bradley J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
This edited volume contributes to a burgeoning field of critical scholarship on the news media and education. This scholarship is based on an understanding that the news media has increasingly applied a neoliberal template that mediates knowledge and action about education. This book calls into question what the public knows about education, how the public is informed, and whose interests are represented and ultimately served through the production and distribution of information by the news media about education. The chapters comprising this volume serve to enlighten and call to action parents, students, educators, academics and scholars, activists, and policymakers for social, political, and economic transformation. Moreover, as the neoliberal agenda in North America intensifies, the chapters in this book help to deepen our understanding of the logics and processes of the neoliberal privatization of education and the accompanying social discourses that facilitate the reduction of social relations to a transaction in the marketplace. The chapters examine the news media and the reproduction of neoliberal educational reforms (A Nation at Risk, Teach For America, charter schools, think tanks, and PISA) and resistance to neoliberal educational reforms (online activism and radical Black press) while also broadening our conceptual understanding of the marketization and mediatization of educational discourses. Overall, the book provides an in-depth understanding of the neoliberal privatization of education by extending critical examinations to this underrepresented field of cultural production: the news media coverage of education. The contribution of this edited volume, therefore, helps to build an understanding of the contemporary dynamics of capital accumulation to inform public resistance for social transformation.
Keywords: Mass media and education.; Communication and education.; Privatization in education.; Education -- Educational Policy & Reform -- General.; Media studies.; Educational strategies and policy.; elektronické knihy; electronic books